Construction Industry in Ukraine Credit Analysis - Onyshchenko, Volodymyr; Sivitska, Svitlana; Cherviak, Anna (International Journal of Engineering and Technology, 2018)
Construction is one of the national economy key areas since its operating results are of prime importance for the economic and social development of the country. It is due to the fact that this branch is characterized by a long-term manufacturing cycle and significant materials requirements. Construction enhancement in Ukraine is the principal precondition for successful national development, as far as all the interrelated sectors grow proportionally. Present day construction market conditions and construction crediting are analyzed in the work. Enterprises financial capacity sources are defined and the innovative importance is proved. Â Â